2021
DOI: 10.1192/bjo.2021.621
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of COVID-19 pandemic on frontline health care workers in Bangladesh: A cross-sectional study

Abstract: AimsFrontline health care workers exposed to COVID-19 patients could be at increased risk of developing psychological issues. The study aimed to estimate the prevalence of mental health-related problems, specifically depression, anxiety, post-traumatic stress disorder (PTSD), and insomnia among health care professionals during the COVID-19 pandemic in Bangladesh and to compare these between medical and allied health care professionals.MethodThis cross-sectional survey was conducted using Google Form then subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The current study discovered that being a doctor is an independent risk factor for general health problems, depression, and anxiety symptoms among vaccinated HCWs, which was in agreement with prior studies that found doctors to be more vulnerable to COVID-19 ( 37 , 61 , 62 ). Similarly, in a study of 450 HCWs in Ethiopia, Angelo et al ( 63 ) discovered that physicians were nearly fifteen times more likely than other HCWs to accept the COVID-19 vaccine.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current study discovered that being a doctor is an independent risk factor for general health problems, depression, and anxiety symptoms among vaccinated HCWs, which was in agreement with prior studies that found doctors to be more vulnerable to COVID-19 ( 37 , 61 , 62 ). Similarly, in a study of 450 HCWs in Ethiopia, Angelo et al ( 63 ) discovered that physicians were nearly fifteen times more likely than other HCWs to accept the COVID-19 vaccine.…”
Section: Discussionsupporting
confidence: 91%
“…The Bangla version of the Primary Care PTSD Screen for DSM-5 (PC-PTSD-5) ( 36 ) evaluates post-traumatic stress disorder symptoms over the past month by asking five binary questions about re-experiencing, avoidance, physiological reactions, emotional numbness, and trauma-distorted guilt and blame thoughts. This scale was previously used in a Bangladeshi study ( 37 ). The total score ranges from 1 to 5, with a 3 as the cut-off value.…”
Section: Methodsmentioning
confidence: 99%
“…Kaufhold et al [ 13 ] believes that the purpose of this dose exploration study is to evaluate the dose-response relationship between sugammadex and sugammadex. The generally observed level of neostigmine reversal of rocuronium-induced neuromuscular blockade is not fully restored, that is, the quadruple ratio ≥0.2 [ 4 ]. Miyamoto et al [ 14 ] prove that most spontaneous subarachnoid hemorrhages are saccular aneurysms caused by rupture.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, they are prone to negative emotions and even consider refusing to provide medical services for AIDS patients. Therefore, there is an urgent need to find effective ways to help them learn effective and positive coping styles [ 4 ].…”
Section: Introductionmentioning
confidence: 99%